Effects of Post Activation Potentiation warm-up on subsequent sprint performance: a systematic review - Azcarate Argote, I, (2019)
This review aimed to determine whether a Post Activation Potentiation (PAP) warm-up contributes to an improved sprinting performance. A literature search on 3 databases (PubMed, Scopus and SportDiscus) was conducted on January 30 and 31, 2019. After analysing 115 resultant articles, studies were included if they met the following inclusion criteria: a) studies measured the effects of a PAP intervention, b} PAP was used as a warm-up strategy, e) studies tested exclusively sprint running performance and d) participants were not enrolled in team sports. 11 studies met the inclusion criteria. The results of this systematic review suggest that a PAP warm-up can lead to a significant improvement in running sprint performance, especially in short races (~40-m). Regardless of the distan ce, improvements varied mostly between 1.2% and 2.2% of sprint time reduction. However, the large number of modulating factors affecting PAP have concluded in a plethora of opposing results. By reason of this controversy, stating accurate and general guidelines can be unpractical. Nonetheless, athletes and coa ches could find this review interesting so asto gain sorne expertise about the topic, and therefore, try to apply the PAP individually on warm-ups.